Behavioral functions of stimuli signaling transitions across rich and lean schedules of reinforcement. Issue 2 (21st January 2014) - Everly, Jessica B.; Holtyn, August F.; Perone, Michael
Abstract On multiple fixed‐ratio schedules, pausing is extended at the start of a component ending in a small reinforcer (a lean component) but only when this component follows a component ending in a large reinforcer (a rich component). In two experiments, we assessed whether a stimulus correlated with a lean component is aversive and how its function is affected by the preceding component. In Experiment 1, pigeons responded on mixed fixed‐ratio schedules ending in large or small reinforcers. Observing responses converted the mixed schedule to a multiple one by producing a stimulus correlated with the current component. Overall, the lean stimulus did not suppress observing, suggesting that it was not sufficiently aversive. In Experiment 2, an escape procedure was used, and pigeons could convert a multiple schedule to a mixed one by pecking a key to remove the discriminative stimuli. Pigeons escaped from the lean‐schedule stimulus more than they did from the rich one. For two pigeons, this effect was enhanced when a rich component preceded the lean stimulus. The results indicate that a stimulus correlated with the leaner of two reinforcement schedules can acquire aversive functions, but observing and escape procedures may differ in their abilities to detect this effect.